2014
DOI: 10.1200/jop.2013.001347
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Intensity of Online Access to Electronic Medical Records Among Patients With Cancer

Abstract: Introduction: Electronic portals are secure Web-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 20 publications
6
92
2
Order By: Relevance
“…HIT engagement is more common among certain demographic groups. High educational attainment [8][9][10], female gender [7,9,11], individuals with chronic health conditions such as cancer or caregivers for those with a chronic condition [12][13][14], and higher income [15] were predictors of HIT engagement. Older adults (65 years of age and older) are less likely to engage in HIT activities [15][16][17][18], including accessing personal health records electronically [16].…”
Section: Introductionmentioning
confidence: 99%
“…HIT engagement is more common among certain demographic groups. High educational attainment [8][9][10], female gender [7,9,11], individuals with chronic health conditions such as cancer or caregivers for those with a chronic condition [12][13][14], and higher income [15] were predictors of HIT engagement. Older adults (65 years of age and older) are less likely to engage in HIT activities [15][16][17][18], including accessing personal health records electronically [16].…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we demonstrated a near five-fold increase in the number of patients enrolled, with a 10-fold increase in total patient account log-ins, suggesting that patients and their caregivers use this technology more than twice as much as they did in the recent past. 10 Compared with other populations, we found that patients with cancer used electronic portals far more frequently-12 times that of urology patients and more than four times that of families of children cared for in a congenital heart disease program. 9,12 The considerable increase in portal use by both patients and staff likely reflects multiple factors: increased use of electronic text-based communication at a societal level; increased comfort with electronic communication, resulting in use of additional features; and change in institutional electronic health record policy resulting in availability of additional portal functions over time.…”
Section: Discussionmentioning
confidence: 60%
“…10 Compared with nononcology populations, these patients used the electronic portal four to 10 times more frequently. [10][11][12] How this growth in electronic communication has affected oncology practices is not clear. Within the field of oncology, use of such technology raises particular concerns.…”
Section: Introductionmentioning
confidence: 99%
“…How often caregivers within pediatric oncology utilize the portal for result acquisition, whether there are patterns in how they do so over time, or how those patterns correlate with anxiety remains to be determined. Additionally, many studies have reported disparities in adult portal uses with users tending to be white, younger, more educated, and with higher incomes . Whether disparities in use are consistent, or even exaggerated, within pediatric oncology is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many studies have reported disparities in adult portal uses with users tending to be white, younger, more educated, and with higher incomes. 19,[35][36][37][38] Whether disparities in use are consistent, or even exaggerated, within pediatric oncology is unknown.…”
Section: Discussionmentioning
confidence: 99%